2019
DOI: 10.1136/bmjresp-2019-000411
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study: an intensive care unit sleep promotion protocol

Abstract: PurposeDisturbances, such as in-room activity and sound, are significant sources of sleep disruption among critically ill patients. These factors are potentially modifiable. We tested the impact of an intensive care unit (ICU) sleep promotion protocol on overnight in-room disturbance.MethodsOur protocol restricted non-urgent bedside care from 00:00 to 03:59. Patients were assigned to usual care (n=30) or the sleep protocol (n=26). The primary outcomes were measures of in-room activity, sound and light. These t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…1 Disrupted sleep in this setting may increase delirium risk and prolong mechanical ventilation. 1 2 The use of sleep improvement protocols in the ICU, while being shown to reduce noise and patient interruption 3 and lower delirium, 4 have generally not been shown to improve sleep quality. 1 An important barrier to demonstrating ICU sleep protocols improve sleep quality is the current lack of a low-cost, quantitative method to evaluate sleep in the ICU that is both reliable and feasible to use in daily practice.…”
Section: Introductionmentioning
confidence: 99%
“…1 Disrupted sleep in this setting may increase delirium risk and prolong mechanical ventilation. 1 2 The use of sleep improvement protocols in the ICU, while being shown to reduce noise and patient interruption 3 and lower delirium, 4 have generally not been shown to improve sleep quality. 1 An important barrier to demonstrating ICU sleep protocols improve sleep quality is the current lack of a low-cost, quantitative method to evaluate sleep in the ICU that is both reliable and feasible to use in daily practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we observed LAeq levels far above this threshold in ICU patient rooms. Other groups have observed similar trends (15,37,38). It has been known for over 20 years that high noise levels are present in the ICU and that they adversely affect sleep (15,39,40).…”
Section: Discussionmentioning
confidence: 67%
“…One study found patient rooms were being entered at an average of once every 28 minutes during the middle of the night period. 33 Other studies found that patients experienced 43 care interactions per overnight period and that many of these care interactions were nonurgent. 44,45 Disruption of the normal daytime feeding/night time fasting rhythm has numerous adverse metabolic and circadian consequences.…”
Section: Abnormal Zeitgebers In the Intensive Care Unitmentioning
confidence: 99%
“…31 Nocturnal light has been shown to be too high and too variable, especially in the case of more sick patients who spent more time at light levels greater than 20 lux. 32,33 Highlight variability provides a poor circadian signal; in one study, there were several bright pulses of light up to 300 lux during procedures or bedside patient checks. 34 Similarly, a study of light and sound measurements in a medical ICU showed that both were nearly completely disconnected from solar time.…”
Section: Abnormal Zeitgebers In the Intensive Care Unitmentioning
confidence: 99%